2015
DOI: 10.1038/jhg.2015.79
|View full text |Cite
|
Sign up to set email alerts
|

Unique characteristics of the Ainu population in Northern Japan

Abstract: Various genetic data (classic markers, mitochondrial DNAs, Y chromosomes and genome-wide single-nucleotide polymorphisms (SNPs)) have confirmed the coexistence of three major human populations on the Japanese Archipelago: Ainu in Hokkaido, Ryukyuans in the Southern Islands and Mainland Japanese. We compared genome-wide SNP data of the Ainu, Ryukyuans and Mainland Japanese, and found the following results: (1) the Ainu are genetically different from Mainland Japanese living in Tohoku, the northern part of Honsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 29 publications
7
39
0
Order By: Relevance
“…This was further supported by a genome-wide single nucleotide polymorphism (SNP) study that showed the Ainu and Ryukyuans cluster with 100% bootstrap probability on the phylogenetic tree (Jinam et al, 2012). Furthermore, autosomal SNP data also revealed signs of recent admixture between the Ainu and Hondo Japanese (Jinam et al, 2015).…”
Section: The Indigenous Groups Of Japanmentioning
confidence: 49%
See 2 more Smart Citations
“…This was further supported by a genome-wide single nucleotide polymorphism (SNP) study that showed the Ainu and Ryukyuans cluster with 100% bootstrap probability on the phylogenetic tree (Jinam et al, 2012). Furthermore, autosomal SNP data also revealed signs of recent admixture between the Ainu and Hondo Japanese (Jinam et al, 2015).…”
Section: The Indigenous Groups Of Japanmentioning
confidence: 49%
“…2). The indigenous Ainu and Ryukyuan populations retain a genetic identity that most likely traces back to Jomon ancestors, while at the same time show indications of recent admixture with the Hondo Japanese (Jinam et al, 2015). Some questions remain unanswered, however, such as the origins of the Jomon people and the genetic affinities of the Yayoi people.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We think this is an artifact of including close relatives in PCA, a well-known phenomenon. Indeed, a recent reanalysis by Jinam et al (2015) also found that exclusion of close relatives from the analysis removed this clustering pattern (Jinam et al 2015). We discuss this issue in more detail in Text S1.…”
Section: Discussionmentioning
confidence: 98%
“…The first is that almost all of these studies (Hammer et al, 2006; Harihara, Hirai, & Omoto, 1986; Harihara et al, 1988; Horai et al, 1996; Jinam et al, 2015, 2012; Tajima et al, 2004) were based on modern‐day samples. Historically, after the Meiji government started sending settlers to Hokkaido as a national policy in 1869 (Fumoto, 2004), an enormous number of mainland Japanese migrated to Hokkaido, and their apparent genetic influence on the modern‐day Ainu was confirmed by a genome‐wide single‐nucleotide polymorphism (SNP) analysis by Jinam et al (2012).…”
Section: Introductionmentioning
confidence: 99%